(untitled) - HERIYATI UTAMI, RISA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
The learning process can not be separated from facilities and infrastructure in the school specially on the learning activities in SMK prepare students to enter the world of mid. With the laboratory, then the results of students competence will increase. This study aims to describe of using laboratoy skill and know the influence of using laboratory skills on the results of students competence marketing program. The population in this study is students in a class XI of Marketing Program in SMKN 2 Nganjuk, the size of the sample used in this study was 68 respondents. Data analysis tools used in this study is a simple regression analysis and data collection questionnaire and value of report cards for competency standards prepare and operate equipment transactions. Based on the R Square resulting value of 0,534 means that the influence of using laboratory on the results of students competence marketing program by 53,4%, while the remaining 46,6% are caused by the other factors. The results showed that there was an strenght effect of the variable quality of using laboratory of the results of students competence Marketing Program in SMKN 2 Nganjuk. Keywords : using of marketing laboratory, the results of students competence.